Cadres’ Knowledge of Integrated Primary Health Services (Posyandu ILP) and Their Skill in Implementing the Five-Table System - Putri, Raden Roro Dewi Rahmawaty Aktyani; Nurmawati, Thatit; Agustin, Amelia Diah; Chairunnisa, Miftah (STIKes Patria Husada Blitar, 2025)
The importance of cadre roles is a key determinant in ensuring the smooth implementation of the Integrated Primary Service (ILP) Posyandu program. Cadres play essential roles and functions in Posyandu activities, one of which is carrying out the five-table system. However, in practice, the five-table system has not yet been implemented optimally. This condition may be influenced by several factors, including knowledge. The purpose of this study was to examine the relationship among cadres’ knowledge of integrated primary health services (Posyandu ILP) with their skill in implementing the five-table system. A cross-sectional study was the method applied. 55 cadres made up the study population, and a total sampling strategy was used to include all of them in the sample. Questionnaires were used as tools for testing knowledge and skill. The Spearman Rank statistical test produced a positive correlation value of 0.704 and a p-value of 0.000 (α < 0.05). This indicates a significant relationship between knowledge about ILP Posyandu and cadre skills in carrying out the five-table system. The correlation coefficient reflects a strong positive correlation, meaning that as the level of knowledge increases, the skill level also tends to improve. These findings suggest that regular and comprehensive training sessions should be provided to enhance cadres’ knowledge of ILP and their ability to perform the five Posyandu tables effectively.